OBJECTION OF THE INVESTMENT’S ILLEGALITY IN INVESTMENT ARBITRATION: AN EFFECTIVE SHIELD FOR HOST STATES? - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
A considerable number of bilateral treaties on promotion and protection of investments (Bilateral Investment Treaties or BITs) contain a definition of an investment requiring it to be made in accordance with “laws and regulations” of the host state. Even when the obligation of the investor to act in accordance with the host state’s law is not explicitly included in the text of the relevant treaty investment tribunals tend to observe this requirement as a precondition for their jurisdiction. States which are confronted with investors’ claims often use this plea of illegality in order to challenge the arbitral tribunal’s jurisdiction in investment dispute, i.e. to challenge the existence of their consent to arbitrate disputes about investments made illegally. The objection is, however, rarely successful. This is a consequence of a way in which arbitral tribunals interpret the scope of the investor’s obligation. Arbitral awards demonstrate that the success of such defense depends on variety of factors such as: the relevance of the host state’s legislation at issue, the intensity and timing of the breach and the presence of the investor’s intent. On the other hand, the goal of this paper is to show that the requirement of the investment’s legality can be seen in a different, objective light. The law of the host state determines conditions for the lawful acquisition as well as the content of the property right deemed as the protected investment. If an investor alleges the breach of the property right which, due to his actions, could not be created under the applicable national law, there is no protected investment, i.e. the arbitral tribunal lacks jurisdiction ratione materie.